Consumer Behavior Analysis of Korean Beauty Products in Indonesia: Factors that Influence Market Preferences - Awanda, Kharisma Secillia; Pradana, Mahir; Wardhana, Aditya; Joviano, Ridho; Rintaningrum, Ratna (Journal of Posthumanism, 2025)
This research aims to analyze consumer behavior towards Korean beauty products in Indonesia as well as the factors that influence market preferences. The method used is a quantitative survey, namely taking samples of active users of Korean beauty products and Indonesian beauty products using Google Forms. Data were analyzed using linear regression to determine the relationship between customer satisfaction variables, product quality, and marketing strategy. The research results show that good product quality and attractive marketing strategies greatly influence consumer satisfaction in purchasing a product. These findings provide insight for marketers to optimize promotional strategies and product quality to increase consumer satisfaction in product purchases. It is expected that this research can be a reference for developing more effective marketing strategies for beauty products on the market